ANALYSIS OF DISTANCE EDUCATION IN SPECIAL SCHOOLS (FOR PERSONS WITH HEARING IMPAIRMENTS) - Zinaida A. Motylkova (Інформаційні технології і засоби навчання, 2013)
On the basis of the experience gained from practicing teachers from Russia and Ukraine made an attempt to analyze the current status of distance education in a special school (for persons with hearing impairments). It is proposed to develop a project concerning connection schools for children with hearing impairments to resource centers of distance education. One of the conclusions of our study is that the implementation of the ICT opportunities in the learning process must be considered as part of an integrated structure of learning activities that can not enter in conflict with the usual traditional learning. The problem of teachers’ professional development during of distance education organizational process is considered.